«A Sumalao voy helao» - Ceruti, María Constanza (2025)
From an ethnographic perspective based on participant observation, this paper addresses the pilgrimage on foot to the sanctuary dedicated to the Lord of Sumalao, located almost forty kilometers south of the city of Salta, in the center of the Lerma Valley, in northern Argentina. The sanctuary has maintained its regional role as a trade fair since the colonial period, having grown in importance as a center of pilgrimage, becoming the second most popular religious festivity in Salta. The study carefully collects the spontaneous testimonies of the pilgrims and the vicissitudes of a marathon night walk under freezing winter temperatures, shedding light on the rich nuances of popular Andean devotions and their complex insertion in the multiculturalism of northern Argentina.